A Comparative Study of Non Descent Vaginal Hysterectomy and Total Abdominal Hysterectomy (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Hysterectomy is the commonest major surgical procedure in gynecology. There are different approaches to perform hysterectomy. Conventional abdominal and vaginal hysterectomies are considered to be the common gynecological operations. This study was carried out to assess the comparison between total abdominal hysterectomy and non-descent vaginal hysterectomy.Materials and methods: This randomized clinical trial study was conducted in the department of Obstetrics and Gynecology, Khulna Medical College Hospital between I st July 2021 and 31 st  December 2021. A total of 60 patients  who admitted in the indoor facilities of the department of  Obstetrics and Gynecology, Khulna Medical College Hospital for hysterectomy was considered as study population. Among them 30 were in group A (On whom total abdominal hysterectomy was conducted) and another 30 were in group B (On whom non descent vaginal hysterectomy was conducted). The patients having benign uterine pathology, mobile uterus where uterine size was within 14 weeks were included for the study. All operations were performed by expert gynecological surgeon along with his/her assistants. A comparative study was made between group A and B in terms of duration of Surgery, intra-operative complications, time of ambulation. post-operative complications and duration of hospital stay. All the data was recorded in a preformed questionnaire.Results: The mean age was 44.63±6.24 (SD) years and 47.87±6.64 (SD) years in group A and group B. Greater part of the respondents from group A had >12 weeks’ uterus. From group B 26.7% had normal uterus and 26.7% had 8 weeks’ uterus which was the majority.The most common indication for group A was adenomyosis (36.7%) followed by abnormal uterine bleeding (26.7%), fibroid (26.7%) and PID (10.0%).For group B, the most common indications was abnormal uterine bleeding 946.7%) followed in decreasing order adenomyosis (26.7%), fibroid (23.3%) and PID (3.3) duration of surgery was 91.03±10.64 (SD) minutes for group A patients and 65.83±10.25 (SD) for group B patients. A statistically significant difference was observed between groups where longer surgery duration was observed in group A (p